2022
DOI: 10.1007/s00520-022-07510-8
|View full text |Cite
|
Sign up to set email alerts
|

From evidence to practice: early integration of palliative care in a comprehensive cancer center

Abstract: The American Society of Clinical Oncology (ASCO) recommends that all patients with a diagnosis of advanced cancer be referred to a palliative care team within 8 weeks of diagnosis. The bene ts of early integrated palliative care are well recognized, however, there is a lack of consensus to guide operational aspects of a palliative care service within a comprehensive cancer center. In this study, we explore current palliative care referral patterns at an academic cancer center and provide recommendations for op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…[1,2] Multiple controlled clinical trials have demonstrated that early palliative care (EPC) significantly improves the control of symptoms, emotional distress, the perceived quality of life and the satisfaction of patients with advanced cancer. [3][4][5][6][7][8][9][10][11][12][13][14][15] Some of these clinical trials have also confirmed that EPC can increase patient survival, reduce the futile use of chemotherapy and optimize the use of healthcare resources. [1,15,16] Taking into account the position of the WHO and the robust scientific evidence available, most of the scientific societies and consensus documents of experts in cancer recommend care by specialised multidisciplinary EPC teams for all patients with advanced cancer in parallel with etiological treatment (American Society of Clinical Oncology [ASCO], European Society of Medical Oncology [ESMO], National Comprehensive Cancer Network [NCCN], Lancet Commission).…”
Section: Introductionmentioning
confidence: 99%
“…[1,2] Multiple controlled clinical trials have demonstrated that early palliative care (EPC) significantly improves the control of symptoms, emotional distress, the perceived quality of life and the satisfaction of patients with advanced cancer. [3][4][5][6][7][8][9][10][11][12][13][14][15] Some of these clinical trials have also confirmed that EPC can increase patient survival, reduce the futile use of chemotherapy and optimize the use of healthcare resources. [1,15,16] Taking into account the position of the WHO and the robust scientific evidence available, most of the scientific societies and consensus documents of experts in cancer recommend care by specialised multidisciplinary EPC teams for all patients with advanced cancer in parallel with etiological treatment (American Society of Clinical Oncology [ASCO], European Society of Medical Oncology [ESMO], National Comprehensive Cancer Network [NCCN], Lancet Commission).…”
Section: Introductionmentioning
confidence: 99%
“…Multiple controlled clinical trials have demonstrated that early palliative care (EPC) significantly improves the control of symptoms, emotional distress, the perceived quality of life and the satisfaction of patients with advanced cancer [3][4][5][6][7][8][9][10][11][12][13][14][15]. Some of these clinical trials have also confirmed that EPC can increase patient survival, reduce the futile use of chemotherapy and optimize the use of healthcare resources [1,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, SPC is reserved for patients with the most complex symptom burden. However, multiple barriers to realizing the integration of a palliative approach to care in oncology have been identified, including a lack of role clarity between providers, professional reluctance to begin these discussions early in the disease trajectory, and differences in understanding of EIPC between patients and their providers [ 13 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%